2022
DOI: 10.3389/fpsyg.2022.847902
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Operating Mechanism of E-Commerce Poverty Alleviation in Agricultural Cooperatives: An Actor Network Theory Perspective

Abstract: E-commerce poverty alleviation has become a new wisdom in China’s rural poverty alleviation, but there are a few empirical researches on e-commerce poverty alleviation based on farmer cooperatives. Taking four typical poverty counties in Zhejiang Province as an example, based on the actor network theory (ANT), this paper defines the participants and their obligatory passage point (OPP) from the e-commerce poverty alleviation actor network (EPAAN), combs the roles and interest demands of various stakeholders, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As Ncube et al found, farmers' professional cooperatives have important functions in providing technical support, forming external economies of scale, and releasing price incentive signals, which help farmers and cooperators to observe and communicate with each other and promote the generation of social learning [69][70][71]. Cooperatives are involved in agricultural technology concept promotion [72] and fertilizer management for farmers, and they become the source of production and management training, standardized production services [73], and ecological concept dissemination [74][75][76][77].…”
Section: Similarities and Differences With Existing Studiesmentioning
confidence: 99%
“…As Ncube et al found, farmers' professional cooperatives have important functions in providing technical support, forming external economies of scale, and releasing price incentive signals, which help farmers and cooperators to observe and communicate with each other and promote the generation of social learning [69][70][71]. Cooperatives are involved in agricultural technology concept promotion [72] and fertilizer management for farmers, and they become the source of production and management training, standardized production services [73], and ecological concept dissemination [74][75][76][77].…”
Section: Similarities and Differences With Existing Studiesmentioning
confidence: 99%
“…In terms of the tourism poverty alleviation model, (Tang et al, 2021) conducted field research on deep poverty‐stricken areas in Qinghai Province and discussed different types of tourism poverty alleviation precise models through questionnaire surveys and field surveys. (Chen et al, 2021; Hoque et al, 2020; Otwori & Aniko, 2019; Tang et al, 2021) used binary logistic model, SPSS, semistructured interviews and other methods to analyze tourism poverty alleviation under different modes in the Chongqing ecological tourism district, Kenya, Bangladesh, and other regions from the aspects of e‐commerce (Xu Na et al, 2022), ecotourism, community, and NGOs. In terms of tourism poverty alleviation performance evaluation, (Zhang, 2018) and others used an analytic hierarchy process to evaluate the targeted poverty alleviation effect (Hongwei et al, 2022) of rural tourism in Gushi County, Henan Province.…”
Section: Related Workmentioning
confidence: 99%
“…Cooperatives can play a crucial role to increase profitability in agriculture (Bharti 2020). They play vital roles not only in attracting support for farmers to change and improve their products in compliance with standards but also in reducing costs of data collection on related activities (Higuchi et al 2011; Lawangen 2022; Sarkar et al 2022; Xu et al 2022).…”
Section: Introductionmentioning
confidence: 99%